2017
DOI: 10.18203/2320-6012.ijrms20175719
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of meniscal tears

Abstract: Background: Menisci transmit the forces across the joint and cushion the mechanical loading of the joint. Thus, it is important to identify meniscal tear. A thorough understanding of normal meniscal anatomy and surrounding structure is critical for diagnosis. Magnetic resonance imaging is the current modality of choice providing fine resolution and multi-planar imaging for identifying the meniscal injuries and the various pattern of tear, helping to plan the subsequent management. The purpose of the work was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Similarly out of 12 lateral tears, 3 were found in middle zone and 9 in posterior zone. A study carried out by Gadgil and his partners (2018) indicated that most of the patients had medial meniscal tear (123), followed by lateral meniscal tear (25) and both medial & lateral meniscu tear ( 12) (Gadgil et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly out of 12 lateral tears, 3 were found in middle zone and 9 in posterior zone. A study carried out by Gadgil and his partners (2018) indicated that most of the patients had medial meniscal tear (123), followed by lateral meniscal tear (25) and both medial & lateral meniscu tear ( 12) (Gadgil et al, 2018).…”
Section: Discussionmentioning
confidence: 99%